Surgical Management of Recurrence of Primary Intrahepatic Bile Duct Stones - HongTian Xia; HangYu Zhang; XianLei Xin; Bin Liang; Tao Yang; Yang Liu; Jing Wang; XiangFei Meng (Canadian Journal of Gastroenterology and Hepatology)
Background. The surgical treatment of primary intrahepatic bile duct stones is associated with high rates of postoperative complications, stone recurrence, and reoperation. This study aimed to report an 11-year experience in the management of postoperative recurrence of intrahepatic bile duct stones, analyze the causes of the reoperation, and establish appropriate surgical procedures. Materials and Methods. The records of 148 patients with postoperative recurrence of primary intrahepatic bile duct stones treated from January 2005 to December 2015 were retrospectively reviewed. Prior surgical treatment and postoperative data were analyzed to investigate possible causes of recurrence and reoperation. Results. All patients with a prior cholangiojejunostomy (n = 61) developed biliary stenosis (100%). Of the 86 patients without cholangiojejunostomy, 71 (82.56%) had abnormalities in the structure and function of the lower end of the common bile duct, and 86 had hilar and intrahepatic bile duct stenosis. Of all 148 patients, 136 (91.89%) had positive intraoperative bile cultures. Patients were treated with a modified surgical procedure, and the combined excellent and good rate of long-term outcomes reached 85.48% (106/124). The stone recurrence rate of the 124 patients decreased from 100% (124/124) of the prior operation to 5.65% (7/124) during the reoperation. Conclusions. The pathogenesis of primary intrahepatic bile duct stones is associated with biliary infection and intrahepatic bile duct cholestasis. According to the etiology and pathogenic mechanism, surgical procedures that improve long-term outcomes and reduce postoperative recurrence include bile duct exploration with stone extraction, partial hepatectomy, hilar ductoplasty, and Roux-en-Y hepaticojejunostomy.